Pengaruh Komunikasi, Lingkungan Kerja, dan Motivasi terhadap Kinerja Karyawan di PT. Sarana Makmur Sejahtera - Mariana, Tri Novia; Firdaus, Vera; Abadiyah, Rifdah (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study was to analyze the relationship and influence of communication, work environment, and motivation on employee performance at PT. Sarana Makmur Sejahtera. This type of research is quantitative descriptive research with total sampling technique in data collection. The number of respondents in this study was 130 people. The data analysis technique used was multiple linear regression analysis. The results of this study revealed that simultaneously and partially there was a positive and significant influence between the variables of work environment communication and motivation on employee performance at PT. Sarana Makmur Sejahtera.